Sosialisasi Personal Hygiene Untuk Pencegahan Keputihan Yang Dapat Menyebabkan Infeksi Pada Kalangan Remaja Tahun 2023 - Ninsah Mandala Putri Sembiring; Damayanty S; Emma Dosriamaya; Ade Rachmat Yudiyanto; Feprika Yanti Munthe (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Adolescence experiences physiological, psychosocial, cognitive, moral and sexual development. Physiological changes in adolescence are the result of hormonal activity under the influence of the central nervous system. Physical differences between the sexes are determined on the basis of primary sex characteristics, namely the internal and external organs that carry out reproductive functions, such as the ovaries, uterus, breasts and penis. puberty and fat accumulation) but do not play a direct role in reproduction (Wong, 2015) Leucorrhoea in medical circles is known as leukore or fluor albus, which is discharge from the vagina. Leucorrhoea is a candida yeast infection in female genitalia and is caused by a yeast-like organism, namely candida albicans. Under normal circumstances, the vagina produces a clear, odorless, colorless fluid, the amount is not excessive and is not accompanied by itching. Leucorrhoea is the most common complaint in women. Leucorrhoea can occur under normal circumstances (physiological), but can also be a symptom of a disorder that must be treated (pathological) (Clayton, 2018). The method of carrying out this activity is: education in carrying out proper personal hygiene in adolescents to prevent abnormal vaginal discharge which is characterized by itching, odor, and green color so that it has an impact on infection. This activity began with the preparation of proposals and administration of activities in February 2023.